A new Abelisauridae (Dinosauria: Theropoda) from northwest Patagonia (Ameghiniana, 2013)
Abstract. A new theropod Abelisauridae is described, Ekrixinatosaurusnovasi gen. et sp. nov., of northwestern Patagonia (Neuquén Province, Argentina). A preliminar cladistic analysis placed Ekrixinatosaurus together with Majungatholus and Carnotaurini; and the sister group is Ilokelesia. The presence of this specimen in Albian-Cenomanian beds allows us to support the early divergence (pre-Senonian) of this clade, and the hypothesis of the presence of Abelisauridae in continental Africa. The present distribution of Abelisauridae indicates: 1) a vicariance of this clade based on a pre-Cenomanian pan-Gondwanic distribution; 2) dispersion throughout terrestrial bridges. In both cases, the absence of Abelisauridae in continental Africa can be considered a bias of the fossil record. Resumen. UN NUEVO ABELISAURIDAE (DINOSAURIA: THEROPODA) DEL NOROESTE DE LA PATAGONIA. Se describe un nuevo terópodo Abelisauridae, Ekrixinatosaurusnovasi gen. et sp. nov., del noroeste de la Patagonia (provincia del Neuquén, Argentina). Un análisis cladístico preliminar ubica a Ekrixinatosaurus en un nodo junto a Majungatholus y Carnotaurini; y a Ilokelesia como grupo hermano. La presencia de este espécimen en capas del Albiano-Cenomaniano permite sustentar la divergencia temprana (pre-Senoniana) de este clado y la hipótesis de la presencia en Africa continental de Abelisauridae. La presente distribución de Abelisauridae puede reflejar: 1) una vicarianza de este clado a partir de una distribución pan-Gondwánica pre-Cenomaniana; 2) dispersión a través de puentes terrestres. En ambos casos, la ausencia de Abelisauridae en África continental puede considerarse un sesgo del registro fósil.